NEW STUDENT ADMISSIONS INFORMATION SYSTEM WITH CLIENT SERVER BASED SMS GATEWAY - Zulhipni Reno Saputra Elsi; Gita Rohana; Vera Nuranjani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2021)
Palembang State Junior High School 58 every year accepts new students, every year SMP N 58 always uses the form in registration and collects diplomas, SKHUN, and other files in hardcopy format so that they often experience file loss for that we need a new student admission information system based client-server and SMS gateway. This information system was designed using the Software Development Life Cycle (SDLC) method, and an analysis and design were carried out using a Data Flow Diagram. This information system has the function of saving, delete, update, report automatically, and can send information in the form of SMS. The new student admission information system is user friendly so that it can be easily used, so the admission process is more effective and there are no more missing files